Edukasi Pencegahan dan Manajemen Barotrauma dan Dekompresi pada Nelayan Penyelam di Kampung Nelayan Untia Kota Makassar - Akbar Harisa; Takdir Tahir; Syahrul Ningrat; Wafiq Aulia Ramadhani; Muhammad Hidayat; Lilian Arifka Juli Abdullah; Yodang Yodang; Rosyidah Arafat (Jurnal Abdimas Kesehatan (JAK), 2023)
As an archipelago country, Indonesia has almost 70% of its territory consisting of the sea, and most of the population has a livelihood as fishermen. Traditional fishermen generally are at risk of experiencing barotrauma and decompression due to the low of knowledge and lack of dive facilities. This activity aims to improve fisherman divers’ knowledge on barotrauma dna decompression management. Educational methods applied such as teaching, roleplay and discussion. There are 50 traditional fishermen who voluntarily participated, 43 participants (86.0%) have good knowledge about barotrauma and decompression prevention and management, 20 participants (40%) can demonstrate Basic Life Support by guidance, and 12 participants (24%) were able to demonstrate independently. It is hoped that from this activity the fisherman divers community more familiar and understand about barotrauma and decompression as risks from traditionally diving activities.